BreastDefend enhances effect of tamoxifen in estrogen receptor-positive human breast cancer in vitro and in vivo. Issue 1 (December 2017) - Cheng, Shujie; Castillo, Victor; Welty, Matt; Alvarado, Mark; Eliaz, Isaac; Temm, Constance; Sandusky, George; Sliva, Daniel
Abstract Background Tamoxifen (TAM) has been widely used for the treatment of estrogen receptor (ER)-positive breast cancer and its combination with other therapies is being actively investigated as a way to increase efficacy and decrease side effects. Here, we evaluate the therapeutic potential of co-treatment with TAM and BreastDefend (BD), a dietary supplement formula, in ER-positive human breast cancer. Methods Cell proliferation and apoptosis were determined in ER-positive human breast cancer cells MCF-7 by MTT assay, quantitation of cytoplasmic histone-associated DNA fragments and expression of cleaved PARP, respectively. The molecular mechanism was identified using RNA microarray analysis and western blotting. Tumor tissues from xenograft mouse model were analyzed by immunohistochemistry. Results Our data clearly demonstrate that a combination of 4-hydroxytamoxifen (4-OHT) with BD lead to profound inhibition of cell proliferation and induction of apoptosis in MCF-7 cells. This effect is consistent with the regulation of apoptotic and TAM resistant genes at the transcription and translation levels. Importantly, TAM and BD co-treatment significantly enhanced apoptosis, suppressed tumor growth and reduced tumor weight in a xenograft model of human ER-positive breast cancer. Conclusion BD sensitized ER-positive human breast cancer cells to 4-OHT/TAM treatment in vitro and in vivo. BreastDefend can be used in an adjuvant therapy to increase the therapeutic effect of tamoxifen in patients with ER-positive breast cancer.